Age management and its architecture in polish traditional versus knowledge-based companies - Warwas, Izabela (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
This article concerns the management of mature employees and is based on representative research of Polish employers (N=928). At the beginning, age management is defined in the context of the emerging challenges faced by today’s organisations. One of the most important challenges for management is ageing and the development of an appropriate policy which would counter the negative consequences of managing age and make use of the positive attributes of elderly employees – implemented as a coherent age management concept. The aim of this article is to present the differences and similarities in age management between Polish traditional and knowledge-based organisations. Thus, three dimensions of age management are presented: institutional, instrumental, and functional. The results of this study have been compared to other studies, thus shedding additional light on age management in Poland. Traditional and knowledge-based organisations obviously differ, and in our research, the biggest differences were found in their perception of elderly people and in the instrumental dimension of age management architecture. It can be expected that the development and growing popularity of age management will increasingly erase the remaining differences. It is probable that the differences in the institutional and functional spheres will disappear altogether, while the instrumental sphere of age management will remain differentiated. This differentiation is not about the use of an age management instrument as such, but about its characteristics, related to the degree of formalism, the scope of content, and the number of users. Traditional and knowledge-based organisations can also differentiate their accents in different spheres related to human resources management. It seems likely that this will occur in the near future, alongside changes which will dynamically implement those practices aimed at bringing equal and synergistic benefits to both elderly workers and employers
Argumenta Oeconomica, 2019, Nr 2 (43), s. 407-426
Keywords: age management; silver economy; knowledge-based organization; traditional organization; older emloyees; age